REVIEW VALUATION METHOD FOR MARINE ECOSYSTEM SERVICE - Wan Ab Rashid, Wan Nur Ayuni; Mohamad, Junainah (Journal of Civil Engineering, Science and Technology, 2025)
Increased human pressure on marine ecosystems in the coming decades is expected, leading to a decline in ecological functioning and loss of marine biodiversity. Restoration efforts are crucial to address habitat deterioration and support conservation measures. Ecosystem service valuation measures the flows of products and services from natural capital assets under the presumption that decision-makers and stakeholders can control them. By doing that, ecosystem service valuation guarantees that ecosystems’ worth and the services they offer are more fully acknowledged during the policy-making process. Ecosystem service value, for instance, might assist decision-makers in comparing various management approaches. Estimating the cost for insurance policy setting and evaluating the cost of preventing climate disasters could also be made possible via valuation. Formulating a strong valuation approach that fits the local environment and can effectively communicate pertinent information to decision-makers is one of the main recommendations for valuation practitioners. A detailed assessment of the literature has been conducted to provide a comprehensive overview of the body of knowledge addressing the valuation of marine ecosystem services. Based on previous research on present and upcoming practices as well as concerns related to coastal and marine ecosystem service values, a strengths, weaknesses, opportunities, and threats analysis could be conducted. Alternative methods acknowledged for ecosystem valuation are aimed at facilitating a more thorough identification and elicitation of various ecosystem values.